Identifying effects of volatile organic compounds exposure on kidney stone prevalence in U.S. adults: a cross-sectional analysis of NHANES 2007-2020 - Jinliang Ni; Wei Song; Keyi Wang; Weipu Mao; Guangchun Wang; Bo Peng (BMC, 2024)
Abstract Objective Our aim was to comprehensively investigate the relationship between blood volatile organic compounds (VOCs) and kidney stone prevalence for U.S. adults. Methods In this cross-sectional study, 10,052 participants from the 2007-2020 National Health and Nutrition Examination Survey (NHANES) were included. Multivariate logistic regression model was employed to investigate the association between 9 blood VOCs and kidney stones. We explored the dose-response relationship between blood VOCs and kidney stones using restricted cubic spline (RCS) analysis. Additionally, weighted quantile sum (WQS) regression model was performed to assess the overall association of 9 blood VOCs with kidney stones. Finally, subgroup analyses were conducted to identify the findings in different populations at high prevalence. Results Logistic regression analysis and dose-response risk curves revealed that blood benzene (aOR = 1.308, 95% CI: 1.118-1.530, P = 0.001), blood ethylbenzene (aOR = 1.280, 95% CI: 1.054-1.554, P = 0.013), blood m-/p-xylene (aOR = 1.187, 95% CI: 1.008-1.398, P = 0.040), blood 2,5-dimethylfuran (aOR = 1.319, 95% CI: 1.135-1.533, P < 0.001) and blood furan (aOR = 1.698, 95% CI: 1.305-2.209, P < 0.001) were positively associated with the prevalence of kidney stones. WQS regression analysis revealed that exposure to mixed blood VOCs was positively correlated with kidney stone prevalence (OR = 1.34, 95% CI: 1.14-1.57), with furans carrying the greatest weight. Subgroup analyses suggested that kidney stones were more susceptible to the effects of blood VOCs in young and middle-aged, female, overweight and obese, non-hypertensive, and non-diabetic populations. Conclusions In this study, the results indicated that high VOC exposure was positively and independently associated with kidney stones in U.S. adults. This finding highlighted the need for public health strategies to reduce VOC exposure and its role in kidney stone prevention and treatment.